Shortening of generation cycles in inbred lines of maize (Zea mays L.) through embryo rescue technique - Liotino, Micaela; Varangot, Agostina; Beznec, Aylin; Auteri, Micol; Bossio, Adrian Ezequiel; Lewi, Dalia Marcela; Faccio, Paula Daniela (Istituto Sperimentale per la Cerealicoltura, 2020)
Embryo rescue techniques have been used as an approach to raise hybrids from incompatible crosses. These techniques have also proved to be valuable tools for maize improvement, since they allow reducing the duration of the generation cycles for speed breeding. The aim of this study was to identify an efficient embryo rescue protocol to evaluate the response of maize (Zea mays L.) embryo culture and compare its generation time (seed to seed) with the generation time of plants obtained by mature seed germination. To this purpose, we evaluated the germination efficiency, in vitro protocol efficiency, and days to flowering of three advanced maize inbred lines developed at the National Institute of Agricultural Technology of Argentina. A greenhouse traditional strategy was used as control. The embryo rescue technique allowed obtaining nearly four generations per year compared to the two generations obtained in greenhouse. All the plants obtained by the embryo rescue technique were morphologically normal and fertile. The results confirmed the possibility of using embryo rescue strategies to significantly reduce the duration of the generation cycles in maize.